The diffusion of information technology : experience of industrial countries and lessons for developing countries - Hanna, Nagy.; Guy, Ken; Arnold, Erik.; Developing countries (Washington, D.C. : World Bank, 1995)
This study reports on the experience of Canada, Germany, Ireland, the Netherlands, Sweden, the United Kingdom, the United States, and Japan in designing, implementing and adapting information technology (IT) diffusion programs over the last decade. The study examines the determinants of effective IT diffusion and analyzes the national IT policy portfolios to draw lessons and trends. In particular, industrial countries have shifted their emphasis since the late 80s away from national champions towards diffusion and aiding the small and medium enterprises to adopt already available information technologies. The study also reviews the experience to draw guidelines for designing IT diffusion programs for maximum impact. Programs should consider technology life cycles, the business needs of potential users, their technological sophistication, and their current exposure to international best practices. The study concludes by suggesting roles for governments, private sector, and aid agencies to accelerate the benefits of IT diffusion for development.
Includes bibliographical references.
rpm 07/09/16
Loans
Keywords: Information technology; Technology and state